Ex Vivo Study on the Antioxidant Activity of a Winemaking By-Product Polyphenolic Extract (Taurisolo®) on Human Neutrophils - Giuseppe Annunziata; Xavier Capó; Maria Magdalena Quetglas-Llabrés; Margalida Monserrat-Mesquida; Silvia Tejada; Josep A. Tur; Roberto Ciampaglia; Fabrizia Guerra; Maria Maisto; Gian Carlo Tenore; Ettore Novellino; Antoni Sureda (MDPI AG, 2021)
Oxidative stress (OxS) has been linked to several chronic diseases and is recognized to have both major causes and consequences. The use of antioxidant-based nutraceuticals has been licensed as an optimal tool for management of OxS-related diseases. Currently, great interest is focused on the valorization of agri-food by-products as a source of bioactive compounds, including polyphenols. In this sense, we evaluated the efficacy of a novel nutraceutical formulation based on polyphenolic extract from Aglianico cultivar grape pomace (registered as Taurisolo®). In particular, we tested both native and in vitro gastrointestinal digested forms. The two extracts have been used to treat ex vivo neutrophils from subjects with metabolic syndrome, reporting a marked antioxidant activity of Taurisolo®, as shown by its ability to significantly reduce both the levels of reactive oxygen species (ROS) and the activities of catalase and myeloperoxidase in the cell medium after stimulation of neutrophils with phorbol 12-myristate 13-acetate (PMA). Interestingly, we observed an increase in intracellular enzymatic activities in PMA-treated cells, suggesting that Taurisolo® polyphenols might be able to activate nuclear factors, up-regulating the expression of this target antioxidant gene. In addition, Taurisolo® reversed the increase in malondialdehyde induced by PMA; reduced the expression of pro-inflammatory genes such as cyclooxygenase 2 (COX-2), tumor necrosis factor alpha (TNFα) and myeloperoxidase (MPO); and induced the expression of the anti-inflammatory cytokine IL-10. Overall, these results suggest the efficacy of Taurisolo® in contrasting the OxS at blood level, providing evidence for its therapeutic potential in the management of OxS-related pathological conditions in humans.